2011
DOI: 10.1007/s00442-011-2226-3
|View full text |Cite
|
Sign up to set email alerts
|

Within and between species competition in a seabird community: statistical exploration and modeling of time-series data

Abstract: In a changing environment, the maintenance of communities is subject to many constraints (phenology, resources, climate, etc.). One such constraint is the relationship between conspecifics and competitors. In mixed colonies, seabirds may have to cope with interspecific and intraspecific competition for both space and food resources. We applied competitive interaction models to data on three seabird breeding populations: black-legged kittiwake (Rissa tridactyla), common guillemot (Uria aalge) and Brünnich's gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…At the species level, competition may lead to exclusion if one species experiences a greater competitive effect from another species than within its own species [2,3]. Theoretical [3] and empirical [4,5] investigations have indicated the importance of both competition and the environment in predicting species composition, diversity and niche overlap in ecological communities. However, conclusive demonstrations of competitive exclusion are rare.…”
Section: Introductionmentioning
confidence: 99%
“…At the species level, competition may lead to exclusion if one species experiences a greater competitive effect from another species than within its own species [2,3]. Theoretical [3] and empirical [4,5] investigations have indicated the importance of both competition and the environment in predicting species composition, diversity and niche overlap in ecological communities. However, conclusive demonstrations of competitive exclusion are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Since it was shown that the kittiwake is a competitor to the common guillemot [20], the mirror response may reflect that what is good for kittiwake is bad for the guillemot hence the remarkably similar inflection point in sea temperature at ca 4°C for both species. The change in their diet is explained by climatic variables such as sea temperature, that may be a proxy of the local condition in term of prey availability spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Overlap in diet between species j and k is complete when O jk  = 1 and is absent when O jk  = 0 [20], [41]. Values exceeding 0.6 are considered to represent “biologically significant” overlap in diet composition [42].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations